Beyond Fear of Crime: Toward a Reconceptualization of Emotional Responses to Threat in Urban Public Places - Rebecca Lennox (Socius)
What do social scientists communicate when they label a person or community fearful of crime ? I examine the utility of “fear of crime” as a heuristic for representing emotional responses to threat. Applying Sklansky’s concept of cognitive burn-in , which describes the epistemic foreclosures that occur when schemas become entrenched, I argue that the use of “fear of crime” across domains including academic research and public policy ossifies a simplified framework for thinking about risk. This framework overstates the extent to which the public’s negative emotions in the street are directly crime related and conceals intersectional quality-of-life inequalities. Based on interview data, I theorize three emotional responses to threat: reactive fear, anticipatory fear, and anticipatory anxiety . These responses are socially stratified, with marginalized women disproportionately vulnerable to severe emotions. This typology disaggregates actual and prospective harms, distinguishes crime threats from social threats, and reveals the stratification of emotion and threat severity.